2019
DOI: 10.24052/ijbed/v06is03/c-04
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of foreign direct investment in Ethiopia: Systematic review

Abstract: The determinants of FDI include any host country's situations that affect the inflow of FDI, like market size, the economic growth rate, real growth domestic product, infrastructure, natural resource, the political situation etc. In recent years, Ethiopia has started encouraging the inflow of FDI by improving the investment climate and by providing different incentive packages. The focus of this review is to identify the major determinants of foreign direct investment (FDI) in Ethiopia. The results show that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Scholars have called for more research regarding IFDI in Ethiopia (Legese, 2019). The 2016 CSA survey indicated that material supply (specifically imported raw materials) is the most critical problem for IFDI operations in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have called for more research regarding IFDI in Ethiopia (Legese, 2019). The 2016 CSA survey indicated that material supply (specifically imported raw materials) is the most critical problem for IFDI operations in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…IFDIs in Ethiopia fabricated metal products industry (Industry 12) as having the potential to substitute import (Habtamu and Gashaw, 2015). Scholars have called for more research regarding IFDI in Ethiopia (Legese, 2019). The 2016 CSA survey indicated that material supply (specifically imported raw materials) is the most critical problem for IFDI operations in Ethiopia.…”
Section: The Performance Ofmentioning
confidence: 99%
“…Recent history has shown that the basin is highly afected by recurrent foods as well as erosion [22,[39][40][41][42]. Increasing agricultural activities without land conservation and overgrazing leads to erosion and further aggravates fooding.…”
Section: Study Areamentioning
confidence: 99%
“…Legese (2018), using descriptive statistics have tried to review eight studies conducted on the macroeconomic determinants of FDI in Ethiopia between the year 2006 and 2017. The paper identified growth in real GDP, liberalization and trade openness as major determinants of FDI while inflation, poor infrastructure and level of interest rate affecting it adversely.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Theoretically market, efficiency, resource/asset, macroeconomic and political stability are known to be the main factors behind FDI. In an attempt to empirically test these factors a number of studies have been also conducted using country specific and cross-country figures from developing countries and very few considering Chinese outward FDI such as Buckley et al (2007) in developing countries; Kokouma and Xu (2013) in Guinea; Elshamy (2015) in Egypt; and others investigating determinants of FDI in Ethiopia (Teka, 2014; Aga, 2016; Legese, 2018). These studies have identified macroeconomic and institutional variables as significant determinants, which includes; gross domestic product (GDP) and its growth rate, natural resource endowments, labor force, trade openness, exchange rates, inflation rates, economic, geographic or political relations and proximities.…”
Section: Introductionmentioning
confidence: 99%